Impact of social phobia upon self-esteem of nursing collegians’ in Iraq - zan, Hossam; Khudhair, ali (Iraqi National Journal of Nursing Specialties, 2012)
Objective(s): The aim of this study is to assess the impact of social phobia upon self-esteem of nursing collegians. Methodology: A Cross-sectional study is carried out at University of Baghdad, Karkuk, Thi-Qar, and Kufa, colleges of nursing from Feb 8 th , 2011 to Sep. 25th, 2011. A sample of all first class nursing collegians (N=330) were selected from a probability sample of nursing colleges by dividing Iraq to three geographical areas (South, North, and Middle Euphrates) in addition to Baghdad. The data were collected through the use of selfadministered technique as a mean for data collection, by using a questionnaire that consists of three parts: First part was the socio-demographic data form; the second one contains the Index of Self-esteem Scale (ISE); and the third one that is concerned with Social Phobia instrument which includes Social Phobia Inventory (SPI) Scale, and Social Interaction Anxiety (SIA) scale. Reliability of the questionnaire was determined through a pilot study and the validity was achieved through a panel of (17) experts. The data were described statistically and analyzed through use of the descriptive and inferential statistical analysis procedures. Results: The study results show the effect of the index of self-esteem scale was 80 %, whereas the effect of the Social Interaction Anxiety was 15%, followed by the Social Phobia Inventory (5.8%). Social phobia has a significant impact upon nursing collegians’ self-esteem. Conclusion: The study concluded that most of the nursing collegians have low self-esteem and this level was probably affected by the variable of social phobia. Recommendations: The study recommended providing opportunities for students to participate in organizations, conferences, and study projects to elevate their level of self esteem and constructing and implementing educational programs for secondary schools teachers about how to decrease social phobia among their pupils.